PROBLEMS OF AXIOLOGY: PAST AND MODERNITY - Проценко, Е. Б. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article considers the problem of values and human senses in the philosophical and religious studies aspects in past and modern time.